Simultaneous Determination of Sulfonamides in Honey by Dispersive Liquid-liquid Microextraction Combined with High-Performance Liquid Chromatography - Chi, Xiaofeng; Zhang, Guoying; Xiao, Yuancan; Dong, Qi; Hu, Fengzu (Asian Journal of Chemistry, 2014)
Dispersive liquid-liquid microextraction combined with high-performance liquid chromatography-diode array detection has been successfully developed for the extraction and determination of sulfonamides in honey samples. The effects of parameters such as the nature and volume of extraction solvent and dispersive solvent, extraction time, ionic strength and solution pH were investigated. In this method, 1 mL of acetonitrile (as dispersive solvent) containing 40 μL of 1,1,2,2-tetrachloroethane (as extraction solution) was rapidly injected into a 5 mL honey sample containing the analytes, thereby forming a cloudy solution. After extraction, phase separation was performed by centrifugation and the enriched analytes in the sedimented phase were determined by HPLC-DAD. Under the optimal conditions, the detection limit of the method was 0.8-1.7 μg kg-1 and the relative standard deviations (RSD %) for determination of the sulfonamides were in the range of 0.172-1.549 %. Linearity was found to be in the range of 0.1-10.0 μg mL-1; also, the enrichment factors were in the range of 42-81. Finally, the method was applied to determine the trace amounts of the sulfonamides in real honey sample and satisfactory results were obtained.